Cirrhosis Management: Utilization and Optimizing Non-Invasive Tests in Portal Hypertension - Irsan Hasan (Interna Publishing, 2024)
Early identification of clinically significant portal hypertension (CSPH) is crucial in cirrhosis, as it is the primary underlying mechanism of cirrhosis complications. One such complication is esophageal varices, which are associated with high morbidity and mortality. Hepatic venous pressure gradient (HVPG) measurements and endoscopy, considered the gold standard for these conditions, are invasive methods that are limited, costly, and inconvenient. To address this challenge, a combination of non-invasive tests can be employed to predict CSPH and esophageal varices. A validated approach involves combining liver stiffness measurement (LSM) by transient elastography (TE) with platelet count. Additionally, spleen stiffness measurement (SSM) has emerged as a promising method for evaluating high-risk varices, as reported by Nababan et al. Therefore, non-invasive methods can be utilized to identify patients who need invasive procedures or potentially replace invasive procedures altogether.